A Ready-to-Eat Antioxidant Rich Appetizer Based on Coleus aromaticus: Its Development and Shelf Life Evaluation. (8th October 2014) - Kumar, Pawan; Wadikar, Dadasaheb; Patki, Prakash
Abstract : Antioxidant rich products are valued due to their health benefits and appetizers are required in several pathological and geographical stress situations such as prolonged exposure to altitude. The paper deals with the development of a shelf stable RTE (ready-to-eat) antioxidant rich herbal appetizer convenient to the consumer. Using ginger and Karpurvalli ( Coleus aromaticus ) as two independent variables, a central composite design with 13 experimental combinations was obtained. These combinations were processed by concentration and dehydration into the appetizer RTE munches using preprocessed ingredients and evaluated for antioxidant activity, vitamin C, and sensory characteristics. The product optimized using Design Expert Statistical Software had the proximate composition of 11.4% fat, 2.3% protein, and 75.0% carbohydrates, supplying about 82.36 Kcals per munch of 20 g. The munches packed in metalized polyester pouches had a shelf life of 10 months at 28 ± 5°C as well as 37°C storage. The RTE appetizer based on Coleus aromaticus was developed with excellent sensory properties and shelf stability.